Stabilization in the Baltic Countries : A Comparative Analysis - Saavalainen, Tapio (IMF Working Papers; Working Paper ;, 1995)
The Baltic countries began their stabilization and reform process in earnest in mid-1992. During the first two and a half years of reform, these countries have made significant progress in macroeconomic stabilization. Financial policies were tight, inflation was brought down, and by 1994, the output decline had bottomed out and recovery was under way. The paper analyzes the key aspects of this adjustment process in a comparative framework. Apart from comparing the Baltic stabilization programs themselves, major features of their fiscal adjustment, price, and output stabilization are related to the Central European experience. Factors that could explain the good performance in the Baltic countries are suggested and key aspects of an adjustment process typical for an exchange-rate-based stabilization and money-based stabilization, respectively, are discussed. The paper argues that in light of the Baltic experience the credibility of stabilization policies has been of greater importance than the choice of the exchange rate regime per se. Moreover, the cost of disinflation in terms of lost output was limited and short lived.